Nutrient density: addressing the challenge of obesity. (30th October 2017) - Drewnowski, Adam
Abstract: Obesity rates are increasing worldwide. Potential reasons include excessive consumption of sugary beverages and energy-dense foods instead of more nutrient-rich options. On a per kJ basis, energy-dense grains, added sugars and fats cost less, whereas lean meats, seafood, leafy greens and whole fruit generally cost more. Given that consumer food choices are often driven by price, the observed social inequities in diet quality and health can be explained, in part, by nutrition economics. Achieving a nutrient-rich diet at an affordable cost has become progressively more difficult within the constraints of global food supply. However, given the necessary metrics and educational tools, it may be possible to eat better for less. New metrics of nutrient density help consumers identify foods, processed and unprocessed, that are nutrient-rich, affordable and appealing. Affordability metrics, created by adding food prices to food composition data, permit calculations of both kJ and nutrients per penny, allowing for new studies on the economic drivers of food choice. Merging dietary intake data with local or national food prices permits the estimation of individual-level diet costs. New metrics of nutrient balance can help identify those food patterns that provide optimal nutritional value. Behavioural factors, including cooking at home, have been associated with nutrition resilience, defined as healthier diets at lower cost. Studies of the energy and nutrient costs of the global food supply and diverse food patterns will permit a better understanding of the socioeconomic determinants of health. Dietary advice ought to be accompanied by economic feasibility studies.